Are gait characteristics and ground reaction forces related to energy cost of running in elite Kenyan runners? - Santos-Concejero, J.; Tam, N.; Coetzee, D. R.; Oliván, J.; Noakes, T. D.; Tucker, R. (Journal of Sports Sciences, 2017)
The aim of this study was to determine whether gait cycle characteristics are associated with running economy in elite Kenyan runners. Fifteen elite Kenyan male runners completed two constant-speed running sets on a treadmill (12 km/h and 20 km/h). VO2 and respiratory exchange ratio values were measured to calculate steady-state oxygen and energy cost of running. Gait cycle characteristics and ground contact forces were measured at each speed. Oxygen cost of running at different velocities was 192.2 ± 14.7 ml/g·km at 12 km/h and 184.8 ± 9.9 ml/kg·km at 20 km/h, which corresponded to a caloric cost of running of 0.94 ± 0.07 kcal/kg·km and 0.93 ± 0.07 kcal/kg·km. We found no significant correlations between oxygen and energy cost of running and biomechanical variables and ground reaction forces at either 12 or 20 km/h. However, ground contact times were ~10.0% shorter (very large effect) than in previously published literature in elite runners at similar speeds, alongside an 8.9% lower oxygen cost (very large effect). These results provide evidence to hypothesise that the short ground contact times may contribute to the exceptional running economy of Kenyan runners.